A valley-sensed emulated peak current controlled buck converter for automotive applications. (July 2022) - Bhattacharya, Shuvoshree; Maity, Ashis; Patra, Amit
Abstract: This paper presents an emulated peak current-mode control topology targeted for a high voltage buck converter for automotive applications, where one of the key challenges is to protect the devices from the high voltage stress. The proposed controller scheme eliminates the issue of the voltage stress and at the same time reduces the design complexity of the current sensing block. In addition to that, the inherent issue of sub-harmonic oscillations in the current-mode controller has been resolved by the proposed adaptive slope compensation. The input operating voltage of the converter ranges from 5 V to 36 V with output of 3.3 V. The proposed controller, designed in TSMC 180-nm Bipolar-CMOS-DMOS (BCD) process achieves a minimum on-time of 28 ns and a minimum off-time of 120 ns. It can drive a maximum load of 3.3 A while operating at a switching frequency of 2.1 MHz. The peak power efficiency, achieved at 2 A load, is 93.63%.